Hubungan Antara Tingkat Penggunaan Smartphone Dengan Tingkat Perilaku Prososial Anak Kelas V SD - Melemius Riko Mainaki; Dian Mayasari; Mertika Mertika (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research explores the relationship between smartphone use and prosocial behavior in fifth grade elementary school children. The aim is to provide a description of smartphone usage patterns and identify prosocial behavior associated with the use of this technology. The research design uses a correlation method to evaluate the relationship between the two variables. The results of the analysis show that although the level of smartphone use is still low, children's prosocial behavior in the context of smartphone use is at a moderate level. An important finding from this research is that there is a relationship between smartphone usage patterns and the prosocial behavior of fifth grade elementary school children. The implication of these results is the importance of understanding the use of technology in the context of developing children's social behavior. This research uses an instrument in the form of a questionnaire about smartphone use and prosocial behavior. In conclusion, this research highlights the importance of paying attention to smartphone use and the development of prosocial behavior in children in today's digital era. Based on the results of this research, it can be concluded that there is a relationship between smartphone use and prosocial behavior in fifth grade elementary school children. Even though the level of smartphone use is still low, children's prosocial behavior in the context of smartphone use is at a moderate level. These findings demonstrate the importance of understanding the use of technology in the development of children's social behavior.